Meta Analysis the Effectiveness of Mobile-Based Stress Management Application on Stress and Depression among Workers - Untari, Niken Yuliani; Tamtomo, Didik; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The application of stress management at this time really needs a smartphone application to prevent the occurrence of severe mental disorders, reduce stress levels and use this application more effectively. The purpose of this study is to conduct a meta-analysis with the aim of studying and estimating the effectiveness of mobile-based stress management applications on stress and depression in workers.Subjects and Method: This study is a meta-analysis using PICO, Population: Workers, Intervention: Using a mobile-based stress management application, Comparison: Not using a mobile-based stress management application, Output: Stress and Depression. The process of searching for articles between 2012-2022 uses 5 databases: PubMed, Google Scholar, ProQuest, Science Direct and Scopus. The keywords used are “stress” OR “depression” AND “apps” OR “digital health” OR “mobile health” OR “message text” OR “phone calls” OR “website” OR “email” AND “employee” OR “ worker”. Inclusion criteria: article must be a full paper with Randomized Controlled Trial (RCT), article using English, population namely workers, mobile-based stress management application intervention, reported results are stress, depression, include research results number of respondents, average -mean score and standard deviation (SD). Articles that met the requirements were analyzed using the RevMan 5.3 application. Results: There were 14 articles with a Randomized Controlled Trial (RCT) research design originating from Germany, Spain, Switzerland, England, America, Thailand, Taiwan, Korea, Vietnam which were carried out by meta-analysis. The size of the stress sample is 4,865 workers. The meta-analysis shows that workers who use the mobile-based stress management application have 1.08 units lower stress than do not use the mobile-based stress management application, and it is statistically significant (SMD = -1.08; 95% CI = -1.70 to -0.45; p= 0.007). The sample size for depression is 3,983 workers. Workers using the mobile-based stress management application had depression 0.47 units lower than those not using the mobile-based stress management application, and it was statistically significant (SMD = -0.47; 95% CI = -0.85 to -0.10; p = 0.01).Conclusion: Mobile-based stress management application use reduces stress and depresssion in workers.Keywords: stress, depression, stress-based mobile application, worker, employee, meta analysisCorrespondence:Niken Yuliani Untari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nikenyuliani1978@gmail.com. Mobile: +6281215810608Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.06